PERANAN SISTEM INFORMASI AKUNTANSI PENGGAJIAN DALAM PELAKSANAAN PENGENDALIAN INTERN PADA PT KEBON AGUNG - Puspaningrum, Rizky Ayu (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2013)
This research is meant (1) to find out the implementation of salary accounting information system in order to support the fluency of payroll process at PT Kebon Agung Surabaya; (2) to find out the role of payroll accounting information system in carrying out the internal control which is implemented by the company in giving accurate information for management. The result of analysis on payroll accounting system at PT Kebon Agung Surabaya inidcates that there is a weakness in the implementation of payroll accounting system which has been running by the company for long, the weakness is in organization structure which has not separated the functional responsibility firmly yet, which is in the payroll system the company financial record keeping and payroll record keeping is less maximize and some employees do not come to the office on time. The result of attendance system which does not give any sanction to the employees who come late three days consecutively. Moreover, the employees conduct deviation by coming late but not consecutively in order to avoid sanction. Therefore the employees can come late without any sanction which should be given to them. The presence of double duty of financial function and accounting which are performed by one employee who is the personnel department indicates that the internal control is less performed, so the data is less credible and it results in the payroll accounting information system which is difficult to be carried out. So, it has an influence to the weakness of monitoring function which has already been performed by the company. The company should perform changes to the organization structure by separating the finacial department and the accounting department. As this changes will streamline the authorization process at the moment of employees salary payment as well as to give sanction or warning to the employees who come late in order to make them more disciplin in working. Keywords: procedures, system, payroll accounting information system and internal control